Pendekatan Budaya dalam Resolusi Konflik Politik Aceh: Suatu Catatan Reflektif - Muhammad Sahlan; Iromi Ilham; Khairul Amin; Ade Ikhsan Kamil (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2022)
This reflective paper aims to discuss the importance of using a cultural approach to resolve political conflicts and see the past as a learning space to create a civilization in the present and future. In the context of conflict, Aceh has become a medium for learning how the political conflict between GAM and the Indonesian government is resolved. The experience of past conflicts, a series of failed negotiations, and the cultural approach to the Helsinki negotiations, in parallel, serve as important lessons and evidence that “historical-humanism” does not work in a vacuum. This article illustrates that a cultural approach is a key to successful negotiations for a resolution. This is due to several things: first, building an estuary of peace with a cultural approach taking into account the representations and interests of the two conflicting parties, related to technicalities and mechanisms and matters of a substantive nature. Second, understanding and appreciating the perspective of others is important to know what messages and aspirations have not been conveyed properly so far. And third, acknowledging past mistakes and sins, then sincerely and boldly apologizing to those who were hurt, is a form of acknowledging regret for what has been done.AbstrakTulisan reflektif ini bertujuan untuk membahas pentingnya menggunakan pendekatan budaya untuk menyelesaikan konflik politik dan melihat masa lalu sebagai ruang belajar untuk menciptakan peradaban di masa sekarang dan masa depan. Dalam konteks konflik, Aceh menjadi media pembelajaran bagaimana konflik politik antara GAM dan pemerintah Indonesia diselesaikan. Pengalaman konflik masa lalu, serangkaian negosiasi yang gagal, dan pendekatan kultural terhadap negosiasi Helsinki, secara paralel, menjadi pelajaran dan bukti penting bahwa “humanisme-historis” tidak bekerja dalam ruang hampa. Artikel ini menggambarkan bahwa pendekatan budaya adalah kunci keberhasilan negosiasi untuk sebuah resolusi. Hal ini disebabkan oleh beberapa hal: pertama, membangun muara perdamaian dengan pendekatan budaya dengan memperhatikan representasi dan kepentingan kedua pihak yang bertikai, terkait teknis dan mekanisme serta hal-hal yang bersifat substantif. Kedua, memahami dan menghargai cara pandang orang lain penting untuk mengetahui pesan dan aspirasi apa yang selama ini belum tersampaikan dengan baik. Dan ketiga, mengakui kesalahan dan dosa masa lalu, kemudian dengan tulus dan berani meminta maaf kepada yang tersakiti, merupakan bentuk pengakuan penyesalan atas apa yang telah dilakukan.